Tumors Sharply Increased after Ceasing Pazopanib Therapy for a Patient with Advanced Uterine Leiomyosarcoma: Experience of Tumor Flare - Terumi Tanigawa; Shintaro Morisaki; Hisanobu Fukuda; Shuichiro Yoshimura; Hisayoshi Nakajima; Kohei Kotera (Case Reports in Obstetrics and Gynecology)
Pazopanib has activity in patients with soft-tissue sarcoma. We report an advanced uterine leiomyosarcoma case that suddenly worsened after cessation of pazopanib therapy. A 47-year-old woman had a primary uterine leiomyosarcoma tumor and multiple lung metastases, which progressed during her initial treatment. In subsequent treatment with pazopanib for 3 months, the sum of her tumor diameters after cessation sharply increased for two weeks. Symptoms such as dyspnea suddenly worsened also. She died of the disease one month after cessation of pazopanib therapy. Given the poor prognosis of recurrent uterine leiomyosarcoma and the rapid tumor enlargement after ending pazopanib therapy, control of this disease is especially important. Therefore, the decision to discontinue pazopanib therapy requires careful consideration.